Formulation of pomade using soxhlet extraction of yellow pumpkin seed oil (Cucurbita moschata Durch) - Leny, Leny; Ginting, Mandike; Naldi, Jefri; Lubis, Saur (Media Kesehatan Politeknik Kesehatan Makassar, 2023)
Healthy hair is hair that is protected from various problems or diseases. Healthy hair will reveal a shining and luster look, soft texture, easy to style, and grow perfectly. Healthy hair is always depend on daily hair care, therefore it is very important to take care of hair regularly. The purpose of this study was to formulate pumpkin seed oil into pomade preparations. The purpose of this study was to formulate pumpkin seed oil (Cucurbita moschata Durch) in pomade preparations which were tested for its stability. This is an experimental research method by preparing and testing the stability of pomade preparations from pumpkin seed oil with concentrations of 5%, 7.5%, and 10%. The results showed that the pomade preparations from the three concentrations were white to brownish yellow in color, which were homogeneous and semi solid. In spreadability test, F0; F1; and F2 was spreading for 3.3cm while F3 was 2.9cm. The pH of pomade preparations ranges from 6.1-6.7. The irritation test showed that F0, F1, F2, F3 did not cause irritation to volunteers. The pomade resistance test on hair found positive results during four-hour test. The rinsing test showed that all pomade preparations could be rinsed off with water. Pumpkin seed oil pomade (Cucurbita moschata Durch) concentration of 5%, 7.5% and 10% was stable in 12 weeks’ stability test in room temperature.